A matter of faith religion in the 2004 presidential election - Campbell, David E., 1971- (Brookings Institution Press, 2007)
"Examines the religious affiliations of voters and party elites and evaluates the claim that moral values were decisive in the 2004 election. Analyzes strategies used to mobilize religious conservatives and examines the voting behavior of a broad range of groups, including evangelicals, African Americans, and the religious left"--Provided by publisher.